2018
DOI: 10.3389/fphar.2018.00715
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-Terminal Kinases (JNKs) in Myocardial and Cerebral Ischemia/Reperfusion Injury

Abstract: In this article, we review the literature regarding the role of c-Jun N-terminal kinases (JNKs) in cerebral and myocardial ischemia/reperfusion injury. Numerous studies demonstrate that JNK-mediated signaling pathways play an essential role in cerebral and myocardial ischemia/reperfusion injury. JNK-associated mechanisms are involved in preconditioning and post-conditioning of the heart and the brain. The literature and our own studies suggest that JNK inhibitors may exert cardioprotective and neuroprotective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 156 publications
(265 reference statements)
4
78
0
Order By: Relevance
“…They identified that miR-410 suppressed high-mobility group box 1 protein (HMGB1) so that transfection of cardiomyocytes with pcDNA3.1-HMGB1 promoted autophagy, reduced apoptosis, and improved mitochondria function by modulating heat shock protein β1 (Yang, Li, Dong, & Mi, 2018). Moreover, HMGB1 in collaboration with the TNF promoted apoptosis of cardiomyocytes under I/R by JNK activation (Shvedova, Anfinogenova, Atochina-Vasserman, Schepetkin, & Atochin, 2018). miR-30e is another miRNA involved in I/R injury through autophagy, which was downregulated in patients with myocardial I/R injury.…”
mentioning
confidence: 99%
“…They identified that miR-410 suppressed high-mobility group box 1 protein (HMGB1) so that transfection of cardiomyocytes with pcDNA3.1-HMGB1 promoted autophagy, reduced apoptosis, and improved mitochondria function by modulating heat shock protein β1 (Yang, Li, Dong, & Mi, 2018). Moreover, HMGB1 in collaboration with the TNF promoted apoptosis of cardiomyocytes under I/R by JNK activation (Shvedova, Anfinogenova, Atochina-Vasserman, Schepetkin, & Atochin, 2018). miR-30e is another miRNA involved in I/R injury through autophagy, which was downregulated in patients with myocardial I/R injury.…”
mentioning
confidence: 99%
“…These findings suggest that JNK inactivation may be involved in the cellular protection of PDRPS7. JNKs belong to a family of MAPKs, which are activated in response to various stress stimuli such as ultraviolet radiation, oxidative stress, heat and osmotic shock, and cardiac I/R injury . In addition, JNK signaling pathway has been shown to play critical roles in regulating cell fate, being implicated in a multitude of diseases ranging from cancer to ischemic immunological/inflammatory conditions .…”
Section: Discussionmentioning
confidence: 99%
“…JNKs belong to a family of MAPKs, which are activated in response to various stress stimuli such as ultraviolet radiation, oxidative stress, heat and osmotic shock, and cardiac I/R injury . In addition, JNK signaling pathway has been shown to play critical roles in regulating cell fate, being implicated in a multitude of diseases ranging from cancer to ischemic immunological/inflammatory conditions . JNKs cause changes to gene transcription, resulting in biological responses such as inflammation and/or apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations